Nutritional status and the risk of malnutrition in older adults with chronic kidney disease – implications for low protein intake and nutritional care: A critical review endorsed by ERN-ERA and ESPEN. Issue 4 (April 2023) - Piccoli, Giorgina Barbara; Cederholm, Tommy; Avesani, Carla Maria; Bakker, Stephan J.L.; Bellizzi, Vincenzo; Cuerda, Cristina; Cupisti, Adamasco; Sabatino, Alice; Schneider, Stephane; Torreggiani, Massimo; Fouque, Denis; Carrero, Juan Jesus; et al.
Summary: Increased life expectancy is posing unprecedented challenges to healthcare systems worldwide. These include a sharp increase in the prevalence of chronic kidney disease (CKD) and of impaired nutritional status with malnutrition-protein-energy wasting (PEW) that portends worse clinical outcomes, including reduced survival. In older adults with CKD, a nutritional dilemma occurs when indications from geriatric nutritional guidelines to maintain the protein intake above 1.0 g/kg/day to prevent malnutrition need to be adapted to the indications from nephrology guidelines, to reduce protein intake in order to prevent or slow CKD progression and improve metabolic abnormalities. To address these issues, the European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Renal Nutrition group of the European Renal Association (ERN-ERA) have prepared this conjoint critical review paper, whose objective is to summarize key concepts related to prevention and treatment of both CKD progression and impaired nutritional status using dietary approaches, and to provide guidance on how to define optimal protein and energy intake in older adults with differing severity of CKD. Overall, the authors support careful assessment to identify the most urgent clinical challenge and the consequent treatment priority. The presence of malnutrition-protein-energy wasting (PEW) suggests the need to avoid or postpone protein restriction, particularly in the presence of stable kidney function and considering the patient's preferences and quality of life. CKD progression and advanced CKD stage support prioritization of protein restriction in the presence of a good nutritional status. Individual risk-benefit assessment and appropriate nutritional monitoring should guide the decision-making process. Higher awareness of the challenges of nutritional care in older adult patients with CKD is needed to improve care and outcomes. Research is advocated to support evidence-based recommendations, which we still lack for this increasingly large patient subgroup.